Decline and Changing Profile of Hepatitis Delta among Injection Drug users in Spain. Issue 1 (January 2018) - Aguilera, Antonio; Trastoy, Rocio; Barreiro, Pablo; Costa, José Javier; de Mendoza, Carmen; Peña, Jose M; Soriano, Vicente
Background: Roughly 15 million people worldwide have hepatitis delta, the most severe form of chronic viral hepatitis that often leads to cirrhosis and liver cancer. Injection drug users (IDUs) are the largest HDV reservoir. Their resurgence in North America and Europe may represent a new opportunity for HDV to spread more widely. Methods: We examined all consecutive active IDUs seen for the first time and enrolled in detoxification programmes at two clinics in Spain during two periods (1993–1996 and 2011–2014, respectively). Serum markers of HIV, HBV and HDV infection were tested. Results: A total of 209 IDUs were examined in the first period. Mean age was 27-years-old. All had markers of past or current HBV infection. The rate of HIV-antibody (Ab), hepatitis B surface antigen (HBsAg) and HDV-Ab was as follows: 122 (58.4%), 73 (34.9%) and 62 (29.7%), respectively. Serum HDV-Ab was recognized in 53.4% of HBsAg+ and 16.9% of HBsAg- patients ( P <0.001). Positivity for HDV-Ab was associated with HIV regardless HBsAg status. In the second period we tested 47 active IDUs. Anti-HDV was found in only two (4.2%), both immigrants from HDV endemic countries and with HBsAg+. Conclusions: Acute HBV–HDV coinfections and self-limited HDV infections were frequent in the 1990s among IDUs in Spain, especially in HIV+ individuals. In contrast, circulation of HDV has dramatically declined among active IDUs in Spain and is currently very rare, being concentrated in foreign immigrants. It may refect the benefit of universal HBV vaccination as well as the success of needle exchange programmes in Spain.